Penciptaan Pembangunan Desa Wisata Melalui Kerja Aktor Perantara - Sendi Kenia Savitri (Umbara, 2022)
This study departs from a theory of ‘Brokers as Assembler’ which locates brokers as the harmonizers of various orientations of actors in two different social realities, namely disadvantaged populations and power holders in one development practice. Drawing from the role of brokers in the ‘creation’ of tourism village development through social forestry permits, this study offers analysis of brokers beyond their role in carrying out the development; but also in the process of its creation. The development planning, until the development process becomes a productive path that can create benefits for every actor involved. This study was conducted using an ethnographic design and a political ecology approach. The findings of this study suggest that the work of intermediary actors can not only be seen as intermediaries for the vertical relationship between communities holding power and disadvantaged communities. However, brokers also construct horizontal relationships among groups of people in the same social reality to gain access to resources. Thus, studies on intermediary actors must be seen more broadly than their role in agency, transformation, and mediation in the actualization of development.